Evaluation of Environmental Awareness Level among Stakeholders in Rural and Urban Communities, Southern Nigeria - Akpafun, Solomon; Ndinwa, Gabriel C. C; Chukumah, Charity O (International Journal of Climate Research, 2020)
This study was carried out to evaluate the level of environmental awareness of stakeholders in the urban and rural settlements in Delta State, southern Nigeria so as to infer the depth of environmental education that would be embarked on. Five major stakeholders in the state that constituted the major strata of sampling were selected. A total of 14 communities; 7 in the urban/semi urban local governments and 7 in the rural local governments were studied using the stratified sampling technique. Descriptive statistic was adopted for the study and questionnaires were administered to stakeholders. The study revealed that contrary to findings from a number of studies in other part of the globe, students were more knowledgeable on environmental issues followed by public/civil servants and traders/businessmen among stakeholders from the urban settlements. Stakeholders younger in age were not more knowledgeable than older stakeholders in the rural settlements about environmental problems. Male stakeholders had higher percentage level of awareness than their female counterparts. A higher percentage of stakeholders from the rural settlements are still not aware on the environmental terms sought for in this study than stakeholders from urban settlements. This study recommends that given the current level of environmental degradation experienced on a daily base in Nigeria and the limited awareness level of stakeholders on environmental issues, government at various levels should through wider publicity in the ministries of environment and education intensify the campaign on environmental education.